2013
DOI: 10.1371/journal.pone.0073800
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny Drives Large Scale Patterns in Australian Marine Bioactivity and Provides a New Chemical Ecology Rationale for Future Biodiscovery

Abstract: Twenty-five years of Australian marine bioresources collecting and research by the Australian Institute of Marine Science (AIMS) has explored the breadth of latitudinally and longitudinally diverse marine habitats that comprise Australia’s ocean territory. The resulting AIMS Bioresources Library and associated relational database integrate biodiversity with bioactivity data, and these resources were mined to retrospectively assess biogeographic, taxonomic and phylogenetic patterns in cytotoxic, antimicrobial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…The diversity in naturally produced compounds, especially those from marine organisms, has a variety of potential biotechnological, pharmaceutical, commercial, industrial, and environmental applications [253][254][255][256]. To mass produce and utilize bioactive compounds the biology, physiology, and metabolism of the producer marine macro-and microorganisms must be fully understood to adapt target directed and objective cultivation methods.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity in naturally produced compounds, especially those from marine organisms, has a variety of potential biotechnological, pharmaceutical, commercial, industrial, and environmental applications [253][254][255][256]. To mass produce and utilize bioactive compounds the biology, physiology, and metabolism of the producer marine macro-and microorganisms must be fully understood to adapt target directed and objective cultivation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Today's major themes in sponge chemical ecology are to test the bioactivity of natural products regardless of the origin of these metabolites (Wright et al 2011, Freeman and Gleason 2012, Nuñez-Pons et al 2012 and to screen for new drugs with potential pharmacological and biotechnological applications (Leal et al 2012a,b, Acevedo et al 2013, Kampa et al 2013). There are several papers about the variability of bioactive compounds at multiple temporal and spatial scales (Sacristán-Soriano et al 2011a, 2012, Evans-Illidge et al 2013) and many others that link host metabolites with symbionts from the sponge (Hochmuth et al 2010, Penesyan et al 2010, Indraningrat et al 2016. Beneath these main themes, there are some papers dealing with sponge chemistry as a driver of community organization and structure (Paul et al 2007, Pawlik et al 2013) and a few papers focusing on trade-offs in defensive metabolite production (Ivanisevic et al 2011, Gochfeld et al 2012.…”
Section: Sponge Chemical Ecology and Microbial Ecologymentioning
confidence: 99%
“…host plus symbionts) may modulate the organization and functioning of marine benthic communities (Hill 1996, Jimenez and Ribes 2007, Paul et al 2007. Although much of our knowledge on sponge chemistry and associated microbiota is based on a static picture, few studies have documented spatiotemporal dynamics of both bioactive compounds (Sacristán-Soriano et al 2011a, 2012, Evans-Illidge et al 2013) and symbionts of the host (Sacristán-Soriano et al 2011b, Erwin et al 2012b, Bjork et al 2013. As a result, these research lines will further enhance our understanding of the sponge holobiont and will help define a threshold of natural variation.…”
Section: Sponge Chemical and Microbial Ecology: Past Present And Futurementioning
confidence: 99%
“…Phylogenetic selection have also successfully attempted to discover acetylcholinesterase inhibiting alkaloids in Amaryllidaceae [18] and Narcissus -a Mediterranean perennial geophyte [19]. A recent metaanalysis of marine metazoans collected from Australia concluded that the phylogenetic relatedness is the primary determinant of the level of bioactivity due to the evolution of similar metabolic pathways [20]. The study identified deuterostome's lineage as the most promising metazoan lineage for the discovery of bioactive agents.…”
Section: Introductionmentioning
confidence: 99%